Challenges and Opportunities in Relation to Sargassum Events Along the Caribbean Sea - Robledo, Daniel; Vázquez-Delfín, Erika; Freile-Pelegrín, Yolanda; Vásquez-Elizondo, Román Manuel; Qui-Minet, Zujaila Nohemy; Salazar-Garibay, Adán (Frontiers in Marine Science, 2021)
Mass blooms and stranding of pelagic Sargassum spp. in the Atlantic, termed Sargassum events are becoming more frequent in response to several factors. The magnitude of Sargassum events in the Caribbean Sea since 2011 make us aware of the necessity to tackle these events, and macroalgal blooms generally. Due to the regional scale of these events and its complexity, its management should be based on basic and applied information generated by different collaborative actors through interdisciplinary and transdisciplinary work. To address this, we propose different phases and the approach for their study should include detection, collection, stabilization and experimentation. Relevant challenges and opportunities are discussed, remarking on the necessity to evaluate the spatiotemporal variation in the abundance and chemical composition of floating and stranded biomass.